A new tree species of Cupania (Sapindoideae, Sapindaceae) from Quepos, Costa Rica - Chinchilla, Isler F. (Phytotaxa, 2020)
A new species of Cupania, endemic to Costa Rica, is described and illustrated. The species is similar to C. largifolia, but it differs by having vinaceous young leaves, the longest petioles more than 8 cm long, trilobed capsules, each lobe obtuse, dorsally costate, epicarp greenish-yellow, densely puberulent, rugose, and endocarp tomentulose. Notes on its distribution, habitat, phenology, conservation assessment, etymology, and discussion on taxa with similar morphology are provided.